Breaking the Fundamental Limitations of Nanoscale Ferroelectric Characterization: Non‐Contact Heterodyne Electrostrain Force Microscopy (Small Methods 11/2021). Issue 11 (12th November 2021) - Zeng, Qibin; Huang, Qicheng; Wang, Hongli; Li, Caiwen; Fan, Zhen; Chen, Deyang; Cheng, Yuan; Zeng, Kaiyang
Abstract : Inside Front Cover In article number 2100639, Zeng and co‐workers have developed a new SPM technique for nanoscale ferroelectric characterization, namely non‐contact heterodyne electrostrain force microscopy (NC‐HEsFM). NC‐HEsFM breaks the fundamental limitations of the conventionally used piezoresponse force microscopy method by providing a brand‐new non‐contact yet non‐destructive, high‐resolution, non‐optical, electrostatic force effect‐eliminated, highly extreme environments compatible, and multi‐functional ferroelectric characterization solution.